Letter (copy) : Help for the Workers of Spain Fund - Citrine, Walter, 1887-1983
028-0226-001 WMC/HVT/FC/943. Secretary's. 21st August, 1936. Mr. D. Dubinsky, The International Ladies' Garment Workers' Union, 3, West 16th Street, NEW YORK. Dear Mr. Dubinsky, HELP FOR THE WORKERS OF SPAIN FUND. I desire to express my deep appreciation of your cable which reads as follows:- "CABLING TEN THOUSAND MORE REPRESENTS FIVE THOUSAND FURRIERS TWO THOUSAND WORKMENS CIRCLE TWO THOUSAND DRESSMAKERS ILGWU ONE THOUSAND CLOAKMAKERS ILGWU." The money has now come to hand and I have pleasure in enclosing herewith our official receipt. It is indeed a great encouragement to receive this evidence of practical sympathy on the part of our American colleagues, and I should like our most sincere thanks to be conveyed to the above Organisations for their generous gesture. We are, of course, co-operating with the International Federation of Trade Unions and the Labour and Socialist International, and the best possible use will be made of the money sent. Yours sincerely, General Secretary. 292/946/28/226